Sternbergia Clusiana Bulb Ethanolic Extracts Induce Apoptosis in MCF-7 Breast Cancer Cells - Elias, Nazira (2022)
Sternbergia is a genus of plants belonging to the Amaryllidaceae family which is a popular ornamental plant. Plant leaf and bulb extracts of various Sternbergia species have been proven to possess diverse significant biological effects and have been historically employed in traditional medicine. However, the anti-tumor effects of Sternbergia clusiana bulbs in particular has not been investigated to date. The present study explores the anti-cancer activity of the ethanolic extract of Sternbergia clusiana bulbs (SbBEE) on breast cancer MCF-7 cell line in vitro and deciphers the underlying molecular mechanism associated with it. Treatment of MCF-7 cells with SbBEE showed a dose- and time-dependent anti-proliferative effect along with the occurrence of numerous apoptotic hallmarks. A dose-dependent increase in apoptosis via induced DNA fragmentation was revealed via Cell Death ELISA as well as an increase in cellular fragmentation using flow cytometry. On a molecular level, western blot analysis showed an upregulation of pro-apoptotic proteins such as poly(ADP-ribose) polymerase (PARP), Bax/Bcl-2 ratio and caspase-9, with no alterations in caspase-8 levels, revealing the activation of the intrinsic apoptotic pathway. Moreover, SbBEE exposure caused a significant reduction in ROS production proposing a potent anti-oxidant potential. A number of chemical compounds that contributed to SbBEE’s pro-apoptotic activity on MCF-7 cells were detected by liquid chromatography coupled with mass spectrometry, including lycorine, 9S,13R-12-Oxophytodienoic acid (OPDA), fumaritine N-oxide, rhamnetin and ferulic acid. The data presented in this study reveal promising anti-cancerous effects of SbBEE on MCF-7 breast cancer cells in vitro that should be further evaluated in vivo.